PENGARUH MASA PENUGASAN KANTOR AKUNTAN PUBLIK, KEPEMILIKAN MANAJERIAL, DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP KUALITAS LABA - YUSTINA YONATAN (Universitas Katolik Widya Mandala Surabaya, 2012)
Earnings information which reported in a financial report is generally important, especially those who are using financial statements for a contract and decision making of investments. In the purpose of the contract’s perspective, earnings information can be used as basis in determining the salary alocation of an enterprise. In decision making investment’s perspective, earnings information important for investors to know more about the condition of a corporation so they became convinced to invest, therefore earnings profit information in the financial report of the company shall be qualified and in accordance with the accounting standard. This research aims to analyze the factors that affect the quality of earnings on manufacturing companies listed on the Indonesian Stock Exchange period 2006- 2010, those factors are the assignment period of public accounting, managerial ownership percentage, and size of period public accounting. Hypothesis testing in this research is multiple linear regressions. The results of this research indicates that the managerial ownership and public accounting size have positiveeffect on earning quality, means that the greater the percentage of managerial ownership, and the size of a public accounting firrm indicates that the earning information reported in the financial statements are more qualified. The assignment period of accountant public showed negative effect on earning quality, therefore the length the assignmentperiod of public accounting on an enterprise's information led to the earnings information in the financial statementsworst.